Analysis of Activity Daily Living in Elderly with Joint Pain: Rheumatic Exercise and Functional Independence - Romayuli Pardede; Fajar Awang Irawan (Universitas Negeri Semarang, 2026)
The increasing prevalence of joint pain among the elderly often leads to decreased functional independence and limitations in Activities of Daily Living (ADL). Rheumatic exercise is considered a low-impact physical activity that may help maintain joint mobility and functional capacity in the elderly. This study aimed to analyze Activities of Daily Living among elderly individuals with joint pain and to examine the effect of rheumatic exercise on functional independence at Panti Werdha Rindang Asih II Bongsari, Semarang. A quantitative quasi-experimental design with a one-group pretest–posttest approach was employed. The study involved 18 elderly participants selected through purposive sampling. The intervention was conducted over four weeks, with rheumatic exercise sessions held three times per week for approximately 30 minutes. Functional independence was measured using the Barthel Index of Activities of Daily Living. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a significant improvement in ADL scores after the intervention, with the mean score increasing from 71.11 before the intervention to 79.72 after the intervention (p = 0.001). These findings indicate that rheumatic exercise significantly improves functional independence in elderly individuals with joint pain. Rheumatic exercise can therefore be recommended as a safe and effective non-pharmacological intervention to support mobility, independence, and quality of life among the elderly, particularly in institutional care settings.